The Influence of Family of Origin Relationships on Career Thoughts. (February 2017) - Lustig, Daniel C.; Xu, Yonghong Jade; Strauser, David R.
Family of origin relationships are an important influence on career decision-making. The current study investigates the relationship between family cohesion, expressiveness and conflict and dysfunctional career thoughts. The Family Environment Scale - Form R (Moos & Moos, 2009) measured the family environment and the Career Thoughts Inventory (Sampson, Peterson, Lenz, Reardon, & Saunders, 1996) measured dysfunctional career thoughts. Participants were undergraduate students at a large Southern University. The results found that higher levels of family conflict and lower levels of family expressiveness were associated with higher levels of decision-making confusion, commitment anxiety, and external conflict. Implications for career counselors are discussed.